2010
DOI: 10.4300/jgme-d-10-00044.1
|View full text |Cite
|
Sign up to set email alerts
|

The 4∶1 Schedule: A Novel Template for Internal Medicine Residencies

Abstract: Background It is widely acknowledged that there is need for redesign of internal medicine training. Duty hour restrictions, an increasing focus on patient safety, the possibility of inadequate training in ambulatory care, and a growing shortage of primary care physicians are some factors that fuel this redesign movement. Intervention We implemented a 4∶1 scheduling template that alternates traditional 4-week rotations with we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(79 citation statements)
references
References 18 publications
2
75
2
Order By: Relevance
“…22,23 Given the noted strain between competing inpatient and outpatient responsibilities, 24 the continuity clinic experience for IM residents can become stressful and there is variable program compliance with ACGME ambulatory training requirements. 25 In an attempt to uncouple inpatient and outpatient training, a few new program models have developed, which include a year long ambulatory block 26 and an alternating 4:1 week inpatient to ambulatory schedule [27][28][29] that might help to support ambulatory education. Emphasizing outpatient training and education during residency while simultaneously providing protected time to practice ambulatory medicine may help retain resident interest in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 Given the noted strain between competing inpatient and outpatient responsibilities, 24 the continuity clinic experience for IM residents can become stressful and there is variable program compliance with ACGME ambulatory training requirements. 25 In an attempt to uncouple inpatient and outpatient training, a few new program models have developed, which include a year long ambulatory block 26 and an alternating 4:1 week inpatient to ambulatory schedule [27][28][29] that might help to support ambulatory education. Emphasizing outpatient training and education during residency while simultaneously providing protected time to practice ambulatory medicine may help retain resident interest in primary care.…”
Section: Discussionmentioning
confidence: 99%
“…This has been a challenging problem in most resident clinics, but recent innovations such as the ambulatory long block and the "4+1" system of inpatient to ambulatory rotations may improve continuity. 18,30 Of note, other studies have shown associations with gender and years in training and a generalist career. 31,32 Our unadjusted model demonstrated the association with gender and GIM career choice, but the relationship was not evident in the adjusted model.…”
Section: Discussionmentioning
confidence: 96%
“…We included composite indices of learning opportunities (nine items), faculty teaching (10 items), and staff roles (eight items) by Roth et al [20]. We included two previously published items on likelihood of entering a general medicine career [21], one item on number of patients seen in a typical half-day session [22], and two items on satisfaction with the clinic [21,23] which used 5-point Likert scales ranging from ‘disagree strongly’ = 1 to ‘agree strongly’ = 5. The survey was pilot tested for face and content validity with five chief residents at one of the programs.…”
Section: Methodsmentioning
confidence: 99%